The Effect of Financial Literacy on Personal Financial Management - meti, Yonas; Silvia, Rina (International Journal of Social Science and Business, 2022)
One of the intelligences that modern humans must possess is financial intelligence. Financial intelligence is intelligence in managing personal financial assets. This study aims to examine the direct and indirect effect of financial knowledge and financial planning on the personal financial management behaviour of Halmahera University students. This type of research is descriptive quantitative, with the population including all students of the management and accounting study program at Halmahera University, and the research sample includes, all students of the management and accounting study program who have taken financial management courses. Data were analyzed using multiple regression analysis and classical assumption test. From the results of the previous research and discussion, it can be concluded that Financial Knowledge has no effect on the Financial Management Behaviour variable. it can be seen from the results of multiple linear regression tests. Financial Knowledge Variable (X1) has a beta value coefficient of 0.159 from X1 variable with a value of 0.159 > 0.05 and Financial Planning Variable (X2) has a coefficient of 0.144. The value of the X2 variable is 0.144 > 0.05. This shows that the financial knowledge and financial planning variables have no effect on the financial management behaviour variable.